ADHD severity as it relates to comorbid psychiatric symptomatology in children with Autism Spectrum Disorders (ASD). (January 2017) - Mansour, Rosleen; Dovi, Allison T.; Lane, David M.; Loveland, Katherine A.; Pearson, Deborah A.
Abstract: Comorbid diagnoses identified in pediatric samples have been correlated with a range of outcomes, including greater levels of emotional, behavioral, and educational impairment and the need for more intensive treatment. Given that previous research has documented high levels of comorbid Attention-Deficit/Hyperactivity Disorder (ADHD) in children with Autism Spectrum Disorders (ASD), this study closely examines the relationship between parent-reported ADHD symptoms (i.e., Conners' Parent Rating Scale, Revised [CPRS-R]) and the prevalence of additional comorbid psychiatric diagnoses in a pediatric ASD sample (n = 99). Regression analyses revealed that greater severity of ADHD symptomatology was significantly related to a greater number of comorbid psychiatric diagnoses, as identified using the Diagnostic Interview for Children and adolescents, 4th Edition (DICA-IV). Additionally, more severe ADHD symptoms were also associated with higher levels of symptom severity on Child Behavior Checklist (CBCL) syndrome subscales. Interestingly, increasing severity of ASD symptomatology, as measured by the Autism Diagnostic Interview, Revised (ADI-R), was not associated with a higher prevalence of comorbid psychiatric diagnoses or CBCL syndrome severity. Our study concluded that higher levels of ADHD severity—not ASD severity—were associated with a higher prevalence of comorbid psychiatric symptomatology in school-age children with ASD. These findings may encourage clinicians to thoroughly assess ADHD symptomatology in ASD children to better inform treatment planning.